The Implementation of Money Grant Program to Customary Villages and Community Groups From Good Governance Perspective: Case Study in Badung Regency - I Nyoman Adi Wiratma; A.A.N. Oka Suryadinatha Gorda (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2020)
This study determined the implementation of money grants provision to customary villages and community groups, as well as strategies for realizing good governance in Badung Regency. A qualitative approach was used in data collection, utilizing documentation and interviews with 15 informants. The results show that the implementation of grants has met good governance, though some areas need improvement. The good governance principle not optimally implemented is transparency, while participation and accountability have been well executed. However, efficiency and effectiveness are still economically down. This is because there are no sustainable economic benefits. Some of the grants are used for physical development, such as temples or village halls without sustainable economic benefits. Strategies have been put in place by the Badung Regency Government to realize good governance in providing grant money. This include improving quality and strengthening regulations in grant money administration. Furthermore, transparency is increased by utilizing information technology communication. This is accomplished through website and electronic grant applications. Also, accountability is enhanced to strengthen the internal capacity of grant managers. The Badung Regency Government increases community participation from planning, implementation, administration evaluation, and monitoring.